Effects of Storing Three Phytase Sources Over 90 Days Under High Temperature and Humidity on Phytase Stability, Growth Performance, and Bone Mineralization of Nursery Pigs - C. M. Vier; M. B. Menegat; K. M. Gourley; S. S. Dritz; M. D. Tokach; J. R. Bergstrom; R. D. Goodband; J. M. DeRouchey; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2018)
A study was performed to evaluate the effects of storing three commercially available phytase products for 90 d, simulating summer conditions on phytase stability, growth performance, and bone mineralization of nursery pigs. The phytase products [HiPhos GT (20,000 FYT/g, DSM Nutritional Products, Parsippany, NJ); Axtra Phy TPT (20,000 FTU/g, Dupont, Wilmington, DE); and Quantum Blue G (40,000 FTU/g, AB Vista, Plantation, FL)] were left as pure forms or blended in a vitamin and trace mineral (VTM) premix for a 90 d period in an environmentally controlled chamber set at 85°F and 75% humidity. Sampling occurred on d 0, 30, 60, and 90 of storage. Regardless of phytase source and form (pure or VTM), there were linear decreases (P<0.001) in retained phytase activities as the duration of storage increased. At the end of the 90-d storage period, the retained phytase activities ranged from 41 to 60% when phytases were in a pure form and from 38 to 54% when they were in a concentrated VTM premix. For the growth trial, a total of 300 nursery pigs (DNA 241 × 600; DNA) with an initial pen average body weight (BW) of 25.9 lb were used. Pigs were randomly allotted to pens at weaning and fed common diets for 21 d. For 4 d prior to the initiation of the trial, all pigs were fed a common diet deficient in phosphorus (0.12% available phosphorus, aP). At d 0 of the trial, the pens of pigs were randomly assigned to 1 of 8 dietary treatments in a randomized complete block design, with BW used as a blocking factor. There were 4 or 5 pigs per pen and 8 pens per treatment. Experimental diets were formulated to contain 0.12% aP (negative control, NC) or 0.27% aP (positive control, PC) supplied by an inorganic P; or the 0.12% aP diet with added phytase to provide the activity recommended by the manufacturer of each phytase source to release 0.15% aP. These diets were manufactured with each phytase source previously stored either in a pure form or in a VTM premix for 90 days. On d 21 of the study, one pig per pen was euthanized and the right fibula and femur were collected for percentage bone ash calculations. Overall, pigs fed the PC diet had greater (P<0.001) average daily gain (ADG) compared to pigs fed Axtra Phy stored in a VTM premix for 90 days or the NC diet, with other treatments intermediate. Average daily feed intake was similar across the PC, the phytases stored for 90 days in pure forms, and the HiPhos and Quantum Blue stored for 90 d in a VTM premix, and greater (P<0.001) than pigs fed the NC. Pigs fed the PC or the HiPhos stored for 90 d in a pure form had improved (P<0.001) feed efficiency (F/G) compared to pigs fed the NC diet, with the remaining treatments intermediate. Final BW was similar across all added phytase treatments and the PC, which were all greater (P<0.001) than the NC. Bone mineralization was greater (P<0.001) for pigs fed the PC diet compared to the NC, the phytases that were stored for 90 d in a VTM premix, and the Axtra Phy and Quantum Blue stored for 90 d in a pure form, with HiPhos stored in a pure form for 90 d intermediate. In conclusion, this study indicates that regardless of phytase source and form (pure or VTM premix), phytase activity decreases as duration of storage in high temperature and high humidity conditions increases for up to 90 d. Pigs fed PC diets consistently had increased growth performance and bone mineralization compared to pigs fed the other dietary treatments. However, F/G and bone ash of pigs fed HiPhos stored for 90 d in a pure form were similar to results for pigs fed the PC diet, with pigs fed the other phytase treatments intermediate.
Keywords: enzyme; phytase; efficacy; growth performance; nursery pigs